Free circulating ICAM-1 in serum and cerebrospinal fluid of HIV-1 infected patients correlate with TNF-α and blood-brain barrier damage - M. K. Sharief; M. Ciardi; M. A. Noori; E. J. Thompson; A. Salotti; F. Sorice; F. Rossi; A. Cirelli (Mediators of Inflammation)
The mechanism for the initiation of blood-brain barrier damage and intrathecal inflammation in patients infected with the human immunodeficiency virus (HIV) is poorly understood. We have recently reported that tumour necrosis factor-α (TNF-α) mediates active neural inflammation and blood-brain barrier damage in HIV-1 infection. Stimulation of endothelial cells by TNF-α induces the expression of intercellular adhesion molecule-1 (ICAM-1), which is an important early marker of immune activation and response. We report herein for the first time the detection of high levels of free circulating ICAM-1 in serum and cerebrospinal fluid of patients with HIV-1 infection. Free circulating ICAM-1 in these patients correlated with TNF-α concentrations and with the degree of blood-brain barrier damage and were detected predominantly in patients with neurologic involvement. These findings have important implications for the understanding and investigation of the intrathecal inflammatory response in HIV-1 infection.